2007
DOI: 10.1121/1.2710746
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the length of the organ of Corti in humans

Abstract: Sato et al. [Acta. Otolaryngol. 111 (6), 1037–1040 (1991)] reported that the human cochlea is, on average, 15% longer for males than females. This corresponds to 4.7mm in length and to 2.78 standard deviations (SD). Anatomical measurements of the lengths of cochleas from 148 heads (194 cochleas) from eleven sources are reviewed and summarized. A sex difference of 3.36% is observed. This corresponds to 1.11mm in length and to 0.49SD. The mean lengths of the male and female cochleas are approximately 34 and 33mm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
3
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 21 publications
3
28
3
6
Order By: Relevance
“…Sato et al, (1991) used a 3D imaginary technique to analyse the length of male and female cochleae and concluded that the male cochlea was, on average, approximately 14% longer than that of the female. However, these fi gures have been questioned, and comparative studies have been prompted to confi rm the results (Miller, 2007). In terms of the body function domain, several studies have observed differences between the two sexes.…”
Section: Study Characteristicsmentioning
confidence: 97%
“…Sato et al, (1991) used a 3D imaginary technique to analyse the length of male and female cochleae and concluded that the male cochlea was, on average, approximately 14% longer than that of the female. However, these fi gures have been questioned, and comparative studies have been prompted to confi rm the results (Miller, 2007). In terms of the body function domain, several studies have observed differences between the two sexes.…”
Section: Study Characteristicsmentioning
confidence: 97%
“…8 Keadaan tersebut kemungkinan terjadi oleh karena perbedaan anatomi pada jaras pendengaran perifer, volume liang telinga pada laki-laki relatif lebih luas apabila dibandingkan dengan perempuan, 9 di samping itu koklea pada perempuan lebih pendek bila dibandingkan koklea laki-laki. 10,11 Hal tersebut dapat menyebabkan stimulus pada perempuan lebih cepat sampai, juga menyebabkan kekakuan pada membran basilaris dan dapat menyebabkan masa laten gelombang ABR timbul relatif lebih dini. 12 Data yang diperoleh dari penelitian ini juga memperlihatkan tidak terdapat perbedaan yang bermakna masa laten rata-rata dan masa laten antara gelombang ABR antara telinga kanan dan kiri, baik pada balita laki-laki maupun balita perempuan pada semua kelompok usia.…”
Section: Pembahasanunclassified
“…Several studies also reveal anatomical differences in the auditory system between genders. For example, Miller (2007) reviewed 11 studies examining 198 cochleae and found that, on average, male cochleae are longer than those of females by 3.36% or 1.1 mm. Although there is a broad literature on gender differences in hearing, we found no reports of gender differences in the perception of long-duration tones measured using either monaural or binaural techniques.…”
Section: Introductionmentioning
confidence: 97%